Religious Moderation and the Prevention of Dehumanization: A Theological and Socio-Religious Perspective in the Indonesian Context - Adnan, Adnan; Sulaiman, Sulaiman; Yahya, Imam; Widianto, Eko (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
This study examines religious moderation as a theological and socio-religious strategy to prevent dehumanization in contemporary society. This stems from the rampant intolerance, radicalism, and erosion of human empathy that threaten the social order and global human values. The study aims to explain how the principles of religious moderation rooted in Islamic theology—such as ummatan wasathan (the universal welfare) and rahmatan lil 'alamin (the mercy for all the universe)—can function as a transformative paradigm for restoring human dignity. The method used is a qualitative study based on a literature review of 30 scientific articles published between 2018 and 2025 that discuss the relationship between moderation, humanization, and religious ethics. The results show that religious moderation is not merely a moral virtue but a theological imperative capable of suppressing the symptoms of dehumanization by strengthening the values of justice, tolerance, and universal humanity. In conclusion, religious moderation makes a significant contribution to strengthening social cohesion, fostering ethical interfaith dialogue, and building a just and peaceful civilization amidst the diversity of Indonesian and global societies. Keywords: religious moderation, dehumanization, Islamic theology, humanity, tolerance.